2021
DOI: 10.1108/ejtd-07-2021-0101
|View full text |Cite
|
Sign up to set email alerts
|

The paradoxical consequences of leader feedback seeking for subordinates: a theoretical framework

Abstract: Purpose Scholars in the feedback seeking domain have predominantly focused on subordinate feedback seeking. The authors still know very little about feedback seeking when the leader is the “seeker” and subordinates are the “targets” of such seeking. This paper aims to develop a theoretical framework that explores the potential benefits and costs of leader feedback seeking, specifically, leader feedback inquiry for subordinates. Design/methodology/approach The authors draw upon the transactional theory of str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 94 publications
0
1
0
Order By: Relevance
“…Employees generally appreciate comments from their superiors, because this can help them to improve both their performance and the efficiency of their organization [ 14 ]. Therefore, employees would rather connect with and receive recognition from those in higher-ranking positions inside the organization than with and from their colleagues [ 15 , 16 ]. However, recent studies in organizational behavior have confirmed the reality of SDF and investigated its beneficial effects on employees’ behaviors [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Employees generally appreciate comments from their superiors, because this can help them to improve both their performance and the efficiency of their organization [ 14 ]. Therefore, employees would rather connect with and receive recognition from those in higher-ranking positions inside the organization than with and from their colleagues [ 15 , 16 ]. However, recent studies in organizational behavior have confirmed the reality of SDF and investigated its beneficial effects on employees’ behaviors [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%